Ultrasound assessment of muscle mass in the diagnosis of sarcopenia in cardiovascular patients - A. S. Erokhina; E. D. Golovanova; M. A. Miloserdov (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To study the advantages of ultrasound versus anthropometric assessment of muscle mass for early diagnosis of sarcopenia in patients >45 years of age.Material and methods. The study included 79 patients aged 4589 years with coronary artery disease (CAD), hypertension, type 2 diabetes, heart failure, class 1-3 obesity. Diagnosis of hypertension was carried out according to the European (2018) and Russian (2019) guidelines; CAD — according to Russian Society of Cardiology (2020) guidelines. Sarcopenia was diagnosed according to 2010 European Working Group on Sarcopenia in Older People (EWGSOP) criteria and 2018 EWGSOP2 guidelines. Muscle mass (MM) was determined by two methods: 1 — by measuring the rectus abdominis muscle (RAM) thickness using the ultrasound; 2 — by measuring the arm and lower leg circumference. Muscle strength was determined by wrist dynamometer. Muscle function was assessed using the 4-m gait speed test.Results. The study showed that in patients aged >45 years admitted to the emergency cardiology department, the body mass index exceeded 25 kg/m2 in 88,6% of cases. The incidence of sarcopenia of varying severity was 55,7% (n=44). The differences in RAM thickness, arm and lower leg circumference between the groups of patients with/without sarcopenia were significant (p<0,001), but were less than the threshold only for RAM thickness. RAM thickness levels progressively decreased with increasing severity of sarcopenia and significantly differed at all stages compared to patients without sarcopenia (p<0,001), regardless of body mass index. A decrease in lower leg circumference below the threshold values determining a MM decrease was observed only in severe sarcopenia, and arm circumference — in both men and women only in severe sarcopenia. There were no significant differences for arm and lower leg circumference depending on sarcopenia stages in overweight and obese patients.Conclusion. MM assessment by measuring RAM thickness with ultrasound in comparison with the anthropometric method makes it possible to diagnose sarcopenia in patients >45 years of age with cardiovascular diseases and obesity at earlier stages and to promptly recommend preventive measures.